The importance of spatial autocorrelation for regional employment growth in Germany - Ulrich Zierahn (Philipps-University Marburg, Faculty of Business Administration and Economics, 2010)
In analyzing the disparities of the regional developments in the volume of employment in Germany, in the recent empirical literature so called shift-share-regression-models are frequently applied. However, these models usually neglect spatial interdependencies, even though such interdependencies are likely to occur on a regional level. Therefore, this paper focuses on the importance of spatial dependencies using spatial autocorrelation in order to analyze regional employment development. Spatial dependency in the form of spatial lag, spatial error and cross regressive model are compared. The results indicate that the exogenous variables' spatial lag sufficiently explains the spatial autocorrelation of regional employment growth.
Keywords: C21; E24; R11; R23; 330; spatial interdependency; spatial autocorrelation; shift-share-regression; regional employment growth; Regionaler Arbeitsmarkt; Beschäftigung; Räumliche Interaktion; Autokorrelation; Shift-Share-Analyse; Schätzung; Deutschland